Anti-diarrheal Activity of Caffeine: A Modulatory Effect with Loperamide and through 6FH5 (PIK3CG) Protein Interaction Pathway - Faria, Farhana; Hassan, Shardar Mohammad Hafiz; Hossain, Rajib; Mukta, Mahmuda Akter; Chowdhury, Md. Ashiqur Rahman; Islam, Muhammad Torequl (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Caffeine (CAF) is known for its central nervous system stimulatory effect. Although, CAF use in diarrhea, especially in Runner's diarrhea is still controversial, but it has been reported that dark tea containing CAF has anti-diarrheal effect on Sennaemediated diarrhea in mice. Aim: To evaluate the anti-diarrheal effect of CAF and its modulatory effects on the standard anti-diarrheal drug loperamide (LOP), an opioid receptor agonist. Materials and Methods: CAF (15 mg/kg, i.p.) with or without LOP (3 mg/kg, p.o.) was administered to the Swiss mice (Mus musculus) previously treated with castor oil. Additionally, an in silico study was also performed to see the possible anti-diarrheal mechanism of CAF and LOP. Results: CAF increased the latent period, while decreasing the diarrheal defecation during the observation period (4 hr) in the test animals. Interestingly, CAF co-treated with the LOP exhibited a prominent anti-diarrheal effect in comparison to the negative control, CAF and LOP groups. Further, in silico study suggests that CAF have the most binding affinity with the 6FH5 (PIK3CG) protein (-8.22 KJ/mol) of adenosine receptor, while LOP with the μ-opioid receptor. Conclusion: CAF showed significant anti-diarrheal effect as well as strengthen the anti-diarrheal effect of LOP in castor oil-induced diarrheal mice. Protein 6FH5 might be the best conformor for the CAF in the treatment of diarrhea.
Keywords: Mus musculus; Caffeine; Castor oil; Diarrhea; Adenosine receptor